Recommendations for strength and conditioning internships within professional sporting organisations - Koch, C. (Journal of Australian Strength and Conditioning, 2021)
Internships are commonplace in the strength and conditioning industry, however there are currently few reported recommendations of how to host internship programs in these environments (3). Interns can come from a broad background of experience and knowledge (13), and departments hosting interns within professional sporting organisations need to be capable of adapting the contents of their internship programs in line with the intern`s level of prior learning, experience, competencies and future career objectives (14). The purpose of this article is to propose that internships within professional sporting organisations consistently incorporate an application and interview process, induction, probation period, curriculum, practical experience, project work, intern supervision and exit interview. As a consequence of thorough planning and management, the host organisation and intern should achieve a mutually beneficial experience.